The Effect of Oxytocin Massage on Breast Milk Production in Postpartum Mothers at RSUD Dr. M. Thomsen Nias - Erni Hura Erni Hura; Kristhin Suryani Nazara; Iberningsih Zega; Febri Syukur Nirwanna Mendrofa; Helti Wedia Deli Waruwu (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Abstract. Background: Insufficient breast milk production remains a leading cause of exclusive breastfeeding failure in postpartum mothers, particularly in the early postpartum period. Physiological and psychological barriers — including impaired let-down reflexes, post-caesarean effects, and maternal anxiety — reduce milk output and drive supplementation with infant formula. Objective: This study aimed to evaluate the effect of oxytocin massage on breast milk production in postpartum mothers admitted to RSUD dr. M. Thomsen Nias. Methods: A quantitative one-group pretest–posttest quasi-experimental design was employed. A total of 21 postpartum mothers were selected through purposive sampling from the Postnatal Ward of RSUD dr. M. Thomsen Nias from 1 to 14 February 2026. Oxytocin massage was administered along the spine to the 5th–6th costae for 10–15 minutes per session over three consecutive days. Breast milk volume was measured using a manual breast pump before and after each session. Data were analyzed using the Shapiro–Wilk normality test and the paired sample t-test. Results: Mean breast milk production increased significantly from 22.86 ml (SD = 7.171) at pretest to 52.14 ml (SD = 16.013) at posttest, representing a 128.1% increase. The paired sample t-test confirmed a statistically significant effect (t = −8.476; df = 20; p = 0.000; p < α = 0.05). Conclusion: Oxytocin massage is an effective, safe, and easily implemented non-pharmacological intervention for enhancing breast milk production in postpartum mothers, with strong potential for integration into standard postnatal midwifery care protocols. Keywords: Oxytocin massage; Postpartum; Breast milk production; Let-down reflex; Non-pharmacological intervention